REPRESENTATION OF INDIAN IDENTITY IN LITERATURE - Garima Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The concept of ‘Indian identity’ is a product of centuries of historical, cultural, and political transformations. Literature, as an expressive medium, provides unique insights into the growing sense of self and communal identity on the Indian subcontinent. From ancient religious scriptures to current novels, Indian literature has served as a mirror for the country’s varied character, formed by geography, philosophy, social hierarchy, colonialism, nationalism, and postcolonial realities. The variety of Indian identity, which includes ethnic, linguistic, regional, religious, and cultural characteristics, presents both a difficulty and an opportunity when examining how it is represented in literature. This study looks at how Indian identity has been represented and produced in literature during three primary periods: pre-colonial, colonial, and post-independence.